Peran Collaborative Governance dalam Implementasi CSR BUMN untuk Peningkatan Inklusi Keuangan pada Masyarakat Rentan : Studi Kasus Bank BRI Cabang Jombang (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2026)
This study aims to analyze the role of Collaborative Governance in the implementation of Corporate Social Responsibility (CSR) by Bank BRI Jombang Branch as an alternative strategy to enhance financial access. Utilizing the theoretical framework of Ansell and Gash, this study examines how the dimensions of starting conditions, facilitative leadership, and institutional design influence the effectiveness of inter-actor synergy in bridging access gaps that are unreachable through single-actor approaches. This research employs a qualitative method with a case study approach. Data were collected through in-depth interviews with bank management, village officials, and community leaders, supported by field observations and document analysis. The findings indicate that collaboration effectively mitigates information asymmetry and credit risks through a trust-based "social collateral" mechanism managed by local actors. Empirically, this collaborative intervention successfully reduced community dependence on informal high-interest lenders (moneylenders) significantly from 40% to 10% in the target area, and transformed customer behavior from merely holding passive accounts to becoming active users of productive financial services for micro-business development. It can be concluded that Collaborative Governance has successfully shifted the role of State-Owned Enterprise (SOE) CSR from mere transactional philanthropy to an inclusive strategic empowerment instrument. Nevertheless, this success still faces challenges regarding the discrepancy between rigid banking administrative standards and the simpler economic practices of rural communities, as well as a significant digital literacy gap. This study recommends the adoption of a more adaptive institutional design through the simplification of verification procedures for vulnerable groups and the strengthening of hybrid-model mentoring, to ensure the program remains effective and supports the sustainability of community economic independence in the digital era.